World Econonomic and Financial Surveys, 1988 : Staff Studies for World Economic Outlook. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper examines the World Economic Outlook forecasting record for the principal performance indicators for the major industrial countries and corresponding aggregates and for groups of non-oil developing countries. Several criteria were used in evaluating the forecasts: the computation and evaluation of various summary statistics of forecast accuracy, bias, and efficiency; comparisons with alternative forecasts-naive forecasts and forecasts produced by the Organization for Economic Cooperation and Development (OECD) and by national forecasting agencies; the examination of turning-point errors and forecast performance in defined episodes; and, finally, some attempt to explain forecast error in terms of unanticipated developments in policy variables and oil prices. In judging the forecast performance of the World Economic Outlook, a number of points must be kept in mind. Most important, it has to be recognized that the period since the inception of the World Economic Outlook as a regular forecasting exercise has been extraordinarily rich in economic upheavals, which have made the odds against accurate forecasting formidable.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet